Impact of the Roughness of Alumina and Al2O3–C Substrates on the Adhesion Mechanisms in a Model System1 . Issue 9 (18th May 2017) - Ditscherlein, Lisa; Schmidt, Anne; Storti, Enrico; Aneziris, Christos G.; Peuker, Urs A.
Abstract : To improve metal purity by reducing solid and liquid inclusions, intelligent filters with a functionalized surface are studied for an application in metal melt filtration. Besides special coatings that increase the attraction of inclusions at the filter surface or react with gases inside the melt, also the filter roughness might increase the filtration efficiency. In this study, we investigate the influence of roughness on adhesion forces for hydrophilic and hydrophobic filter surfaces in a water‐based model system with an atomic force microscope. In the case of hydrophilic filter substrates, adhesion forces decrease with an increase of roughness whereas on hydrophobic filter surfaces an inverse effect is observed. The primary cause for this is the formation of small cap‐shaped bubbles due to poor wetting. To investigate the stability of these bubbles on smooth as well as rough samples of filter material, imaging in contact mode with increasing applied force is performed. On rough surfaces, the bubbles remain stable even at 30–50 nN because of pinning effects. Abstract : To improve filter material for melt filtration, samples with varying roughness are investigated in a model system via atomic force microscopy. It is observed that the higher the roughness of the samples, the higher the adhesion forces for poor wetting surfaces. Adhesion forces are enlarged by small stable bubbles, which act as capillary bridges between filter and impurity.